Evaluating male sexual function and reproductive health during Omicron outbreak in China. - Jiatong Xiao; Bolong Liu; Juliet Matsika; Ronghua Wu; Zheng Tang; Hui Xu; Xiaowei Dai; Guoou Xie; Fabang Liu; Jingeng Dun; Xiongbing Zu; Jinbo Chen; et al. (PLoS ONE)
There are currently no studies exploring omicron infection and male sexual function and semen quality. Our aim was to estimate changes in sexual function and semen quality in men recovering from infection since the COVID-19 Omicron pandemic started in China in late 2022. We collected 1540 questionnaires and assessed male function before infection and acute phase after infection by using International Index of Erectile Function-5, Premature Ejaculation Diagnostic Tool, and Arizona Sexual Experience Scale. We also collected the before and after semen analysis results of 247 male patients. During the acute phase after infection, the proportion of erectile dysfunction was significantly higher than before infection, but ejaculatory function was not significantly altered; In addition, semen analysis showed significant difference in semen concentration, semen activity and PR a+b sperm forward movement after infection compared to pre-infection.: COVID-19 Omicron can affect erectile function as well as sexual experience in male patients in the acute phase. Decreased sexual function due to COVID-19 Omicron may be related to body temperature and anxiety during infection.